Maintaining a Reputation Against A Long-Lived Opponent - Marco Celentani (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1993)
We analyze in a game between a patient player 1 and a non-myopic but less patient opponent, player 2. We assume that Player 1's type is private information and that players do not directly observe each other's action but rather see an imperfect signal of it. We show that in any Nash equilibrium of the game player 1 will get almost the largest payoff consistent with player 2 choosing a best response in a finite truncation of the game. If the discount factor of player 2 is sufficiently large, then player 1 will get approximately the maximum payoff consistent with player 2 getting at least his pure strategy minmax payoff.
Keywords: 330; Repeated games; commitment; reputation; patience